HUBUNGAN BODY IMAGE, ASUPAN ENERGI DAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2014 - Vicennia Serly; Amru Sofian; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Adolescents is one of the groups vulnerable to negative issues regarding health and nutrition. Nutritional problems suffered by many adolescents is caused by various factors, such as body image, energy intake and physical activity. This study was conducted with the cross-sectional design with a sample selected with a total sampling method. Body image was assessed by questionnaire BSQ-34, obtained through food energy intake records 3x24 consecutive hours, physical activity obtained form 3x24 hour record of activity and nutritional status assessed by measuring BMI. Based on this study of 166 samples were obtained 56% of respondents are not satisfied with the sight of his body image, while the category of energy intake can be seen as much as 57.8% of respondents with moderate energy intake based AKE 2012. For the category of physical activity, can be known that 44% of respondents mild physical activity and as much as 43.4% of respondents normal nutritional status, 18.1% of respondents overweight nutritional status, 15.7% of respondents nutritional status as underweight, 13.9% of respondents nutritional status obese I and the remaining 9% of respondents nutritional status of obesity II. From the results of the analysis carried out there was significant relationship between body image and nutritional status (p = 0.000). There was a significant relationship between energy intake and nutritional status (p = 0.000) and there was significant association between physical activity and nutritional status (p = 0.000). So, there is a significant relationship (p <0.05) between body image, energy intake and physical activity with nutritional status on the students of the Faculty of Medicine, University of Riau Class of 2014.Key words: Adolescents, body image, energy intake, physical activity and nutritional status